The Role of ethical leadership in teachers' organizational dissent behaviors: a comparative analysis - Hava Baydar; Buket Akfırat; Emre ŞAHİN; Engin Danacı; Aziz Şayan (Ilmu Inovasi Nusantara, 2023)
This study aimed to reveal the effect of ethical leadership competencies of educational administrators on teachers' perceptions of organizational dissent. In order to measure the relationship between school administrators' ethical competencies and teachers' perceptions of organizational dissent, a relational survey design, one of the descriptive survey methods, was used. The Ethical Leadership Competencies Scale and the Organizational Dissent Scale were used to collect data on the variables. The sample of the study consists of 387 teachers working in public schools in Pendik, Maltepe, Sultanbeyli and Kartal districts of Istanbul in the 2020-2021 academic year. In the Ethical Leadership Competencies Scale, teachers think that school administrators have ethical competencies to a great extent. In the organizational dissent scale, it is seen that teachers have a moderate level of organizational dissent perception. It was determined that teachers' perceived ethical leadership and organizational dissent levels revealed a low level positive relationship. Based on the data of this study, it can be said that the effect of managers' ethical leadership behaviors on reducing teachers' organizational dissent behaviors in schools is low. Please add conclusion that describe correlation between variable according to gender, graduation, school type, etc